1980
DOI: 10.1111/j.1365-2141.1980.tb07141.x
|View full text |Cite
|
Sign up to set email alerts
|

Heteromorphisms of the Philadelphia (Ph1) Chromosome in Patients with Chronic Myelogenous Leukaemia (CML). I. CLASSIFICATION AND CLINICAL SIGNIFICANCE

Abstract: In patients with chronic myelogenous leukaemia (CML), we have found the break points on the long arm of chromosome 22 (22q) are variable (heteromorphic or polymorphic). Consequently, the Philadelphia (Ph1) chromosome is heteromorphic in size for the long arm. Based upon the break points and the relative size of chromosome 22, four types of Ph1 chromosomes are proposed. They are: Types I (very large), II (large), III (average) and IV (small) with the break points at bands 22q13.3, 22q13.1, 22q12 and 22q11.3, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1981
1981
1988
1988

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…This observation is consistent with the long-accepted fact that acrocentric chromosomes (13-15, 21 and 22) show somatic association. CML represents an interesting situation among human cancers in that a specific chromosome abnormality involving chromosomes 9q and 22q is found in more than 96% of the patients (Verma and Dosik, 1980). In the typical cases of CML with the t(9;22), there has been considerable controversy whether the primary event is the transfer of genetic material from chromosome 9 to 22, or from chromosome 22 to 9.…”
Section: Methodsmentioning
confidence: 99%
“…This observation is consistent with the long-accepted fact that acrocentric chromosomes (13-15, 21 and 22) show somatic association. CML represents an interesting situation among human cancers in that a specific chromosome abnormality involving chromosomes 9q and 22q is found in more than 96% of the patients (Verma and Dosik, 1980). In the typical cases of CML with the t(9;22), there has been considerable controversy whether the primary event is the transfer of genetic material from chromosome 9 to 22, or from chromosome 22 to 9.…”
Section: Methodsmentioning
confidence: 99%
“…Several investigators reported the variety in the size of the Ph chromosome (Watt et al, 1977;Verma and Dosik, 1980). They suggested that the breakpoint may not be specific but can happen anywhere on chromosome //22.…”
Section: Discussionmentioning
confidence: 99%
“…They suggested that the breakpoint may not be specific but can happen anywhere on chromosome //22. Verma and Dosik (1980) described four different types of the Ph according to the size; small, average, large, and very large. However, their very large and large Ph chromosomes were derived from a variant translocation involving //22 and other chromosomes than//9.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation